Efektivitas Sosialisasi Kelembagaan Zakat Oleh Baitul Maal Hidayatullah Bengkulu Melalui Sosial Media - Faiza Tirta Sakinah; Nurul Hak; Andi Harpepen (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study aims to determine the effectiveness of institutional zakat socialization by Baitul Maal Hidayatullah Bengkulu through Instagram social media. This study uses a quantitative approach with an associative descriptive method. The research population is all 1,460 followers of the BMH Bengkulu Instagram account, with a sample of 94 respondents determined using purposive sampling techniques. Data collection was conducted through an online questionnaire using a Likert scale. Data analysis was performed using validity tests, reliability tests, descriptive statistics, and hypothesis testing using F and t tests with the help of SPSS. The results showed that socialization through social media had a positive and significant effect on the effectiveness of zakat institutional socialization. This was proven through the F test with an Fcount value of 66.402 and a significance value of 0.000 (<0.05), as well as the t test which showed a tcount value of 8.149 with a significance of 0.000 (<0.05). In addition, descriptive statistics show that the variables of socialization through social media and the effectiveness of zakat institutional socialization are in the fairly high category. Thus, it can be concluded that the use of social media as a means of digital communication plays an important role in increasing public understanding, attitudes, and participation in zakat through official institutions